Recovery of Lignins with Potent Antioxidant Properties from Shells of Edible Nuts by a Green Ball Milling/Deep Eutectic Solvent (DES)-Based Protocol - Rita Argenziano; Federica Moccia; Rodolfo Esposito; Gerardino D'Errico; Lucia Panzella; Alessandra Napolitano (MDPI AG, 2022)
Lignins are phenolic polymers endowed with potent antioxidant properties that are finding increasing applications in a variety of fields. Consequently, there is a growing need for easily available and sustainable sources, as well as for green extraction methodologies of these compounds. Herein, a ball milling/deep eutectic solvent (DES)-based treatment is reported as an efficient strategy for the recovery of antioxidant lignins from the shells of edible nuts, namely chestnuts, hazelnuts, peanuts, pecan nuts, and pistachios. In particular, preliminarily ball-milled shells were treated with 1:2 mol/mol choline chloride:lactic acid at 120 °C for 24 h, and the extracted material was recovered in 19-27% w/w yields after precipitation by the addition of 0.01 M HCl. Extensive spectroscopic and chromatographic analysis allowed for confirmation that the main phenolic constituents present in the shell extracts were lignins, accompanied by small amounts (0.9% w/w) of ellagic acid, in the case of chestnut shells. The recovered samples exhibited very promising antioxidant properties, particularly in the 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay (EC50 values ranging from 0.03 to 0.19 mg/mL). These results open new perspectives for the valorization of nut shells as green sources of lignins for applications as antioxidants, e.g., in the biomedical, food, and/or cosmetic sector.